TEHNIK ANALISIS DATA KUANTITATIF DAN KUALITATIF DALAM PENELITIAN ILMIAH - Sofwatillah; Risnita; M. Syahran Jailani; Deassy Arestya Saksitha (LPPM Universitas Cipta Mandiri, 2024)
This research aims to analyze quantitative and qualitative research in research. Quantitative data analysis methods are computational and statistical methods that focus on statistical, mathematical or numerical analysis of data sets. So when researchers use this method it will definitely be able to be measured or numbered. that research is divided into two types, namely qualitative and quantitative research. Where each type of research has its own characteristics, both in terms of objectives, content, data, sources and data analysis. Because each research has different objectives. So that each research has different data analysis methods or techniques.